PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS V SD NEGERI 066650 MEDAN KOTA - Nainggolan, Nina Nurhaini; Regina Sipayung; Eka Kartika Silalahi; Patri Janson Silaban; Antonius Religius Abi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the effect of the Project Based Learning learning model on student learning outcomes in the science and science subject class V at SD Negeri 066650 Medan Kota for the 2024/2025 academic year. This research uses quantitative research methods. The research population is class V at SD Negeri 067245 Bunga Asoka which consists of 1 class with a total of 30 students. Sampling used a total sample of 30 students. To determine students' initial abilities, researchers conducted a pretest with an average score of 50.5 in the not good category. After researchers used the Cooperative Integrated Reading and Composition learning model, it showed that student learning outcomes had improved with an average score of 75 in the good category. This research can be proven from the results of the correlation coefficient of 0.841. If rcount ≥ rtable 0.841 ≥ 0.361 then Ha is accepted. This means that there is a strong correlation influence between the project based learning model on the learning outcomes of class V students at UPT SD N 066650 Medan Kota. It can be seen from the results of the t-test, namely 8.215 ≥ 2.048, thus stating that Ha is accepted. This proves that there is a significant influence from the use of the project based learning model on student learning outcomes in the science and sciences subject V SD Negeri 066650 Medan Kota for the 2024/2025 academic year.